An Investigation Of Free Cash Flow Againts Investment Decisions And Company Value - Misrah Misrah; Purnama Sari (STIE Amkop Makassar, 2025)
Investment choices are closely tied to the internal and external funding sources. The market friction affects investment decision, and debt financing decision. The relationship between cash flow and investment efficiency has been extensively examined when making investment decisions. In terms of agency cost justifications, managers frequently spend internal funds when a company has a strong free cash flow. This study aims to synthesize and to test empirically the impact of free cash flow on investment choices and company valuation as a supplemental factor. Manufacturing firms registered on the Indonesia Stock Exchange made up the study's sample. Purposive sampling was utilized to gather the data, and a sample of 117 businesses was obtained. The findings show that the boosting free cash flow had a positive impact on business value. Investment choices were affected by free cash flow. Additionally, the causal relationship between free cash flow and firm value was mediated by investment choices. With an observation period from 2016 to 2022, it can be concluded that free cash flow has a favorable and significant impact on company valuation and investment decisions on the Indonesia Stock Exchange.